Growing Green Streets: Regionalizing Walk/Ride Day. - Adelman, Ian.; DeVore, Sara.; Earle, Emily.; Krogh-Grabbe, Alex.; Morales, Danilo. (Tufts University. Tisch Library., 2018)
2011 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Somerville Department of Health and the Green Streets Initiative.